Integrasi Pengaturan Jaminan Pensiun, Pesangon Dan Perlindungan Hak Pekerja dalam Sistem Jaminan Sosial Nasional - Dwi Yulianta; Momon Mulyana (PT Elaborium Elevasi Indonesia, 2026)
The protection of workers’ rights at the end of employment in Indonesia is implemented through two main instruments, namely severance pay under labor law and pension security under the National Social Security System. However, the regulation of these two instruments still operates separately, resulting in overlapping functions, legal uncertainty, and protection mechanisms that are not systematically integrated. This study aims to analyze how regulatory reform can be carried out to integrate or harmonize pension security and severance pay without reducing the protection of workers’ rights, as well as to examine the legal, social, and economic implications of such reform for workers, employers, and the government. The research method used is normative legal research with statutory and conceptual approaches, through the analysis of relevant primary and secondary legal materials. The findings indicate that the most appropriate regulatory reform should be conducted through partial integration with a clear division of protective functions, by positioning pension security as the primary instrument for protecting workers against the risk of income loss due to normal retirement, while severance pay remains as transitional compensation for termination of employment before retirement age. Such reform would improve legal certainty and sustainability of protection for workers, restructure employment obligations and labor costs for employers, and require regulatory harmonization and strengthening of the social security system for the government.